Enhancing the role of regional development banks - Griffith-Jones, Stephany; Griffith-Jones, David; Hertova, Dagmar (G-24 discussion paper series, 2008)
There are a number of important reasons why lending by regional or sub-regional development banks can and should play an important and valuable complementary role in the international development architecture. The authors look at the specific strengths of multilateral, regional and sub-regional development banks and drawing on the successful experience of the European Investment Bank and the Andean Development Corporation conclude that the time is now for creating new regional development banks and expanding existing ones. Creating new institutions or expanding existing ones will have very clear benefits, as for instance providing regional public goods which are currently undersupplied, such as regional infrastructure. Very large pools of savings and foreign exchange reserves originate in developing countries these days and therefore the potential for a significant expansion of regional or sub-regional development banks, with only or mainly developing country members has grown significantly. At the same time, it may be desirable to create new regional development banks where gaps exist, however too much duplication of services is not desirable.